2022
DOI: 10.1101/2022.11.29.518437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nigral-specific increase in ser31 tyrosine hydroxylase phosphorylation offsets dopamine loss and forestalls hypokinesia onset during progressive nigrostriatal neuron loss

Abstract: Mechanisms that augment dopamine (DA) signaling to compensate for tyrosine hydroxylase (TH) loss and delay motor impairment in Parkinsons disease remain unidentified. The rat nigrostriatal pathway was unilaterally-lesioned by 6-OHDA to determine whether differences in DA content, TH protein, TH phosphorylation, or D1 receptor expression in striatum or substantia nigra (SN) aligned with onset of hypokinesia at two time points. At 7 days, DA and TH loss in striatum exceeded 95%, whereas DA was unaffected in SN, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The 6-OHDA lesion produced a time-dependent loss of TH+ neurons in the SN (Figure 1) (Kasanga et al, 2022). With >90% loss of TH protein confirmed in the striatum (93% by day 7 and 98% by day 28) after lesion induction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 6-OHDA lesion produced a time-dependent loss of TH+ neurons in the SN (Figure 1) (Kasanga et al, 2022). With >90% loss of TH protein confirmed in the striatum (93% by day 7 and 98% by day 28) after lesion induction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the temporal sequence of GDNF or BDNF receptor expression between striatum and SN during nigrostriatal neuron loss has not been established, we determined that expression of the ligands, GDNF and BDNF, were largely unaffected by nigrostriatal neuron loss, and, instead show that the GDNF receptors, GFR-α1 and RET, were differentially affected between striatum and SN over time after lesion induction. Of note, the samples used in this study were obtained from rats that had confirmed parkinsonian motor phenotypes, and significant loss of TH protein in both striatum (>95%) and SN (∼60%) by day 7 and even greater loss (>80%) in SN by day 28 (Kasanga et al, 2022). Notably, GDNF expression was minimally affected after lesion at both time points.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations